SOCIAL DETERMINANTS OF LATE-LIFE DISABILITY IN PUERTO RICO - Matos-Moreno, A (Innov Aging, 2018)
The combined effects of emigration, increased life-expectancy, and low fertility have accelerated the aging of the Puerto Rican population and resulted in increased burdens associated with age-related diseases and risk factors. Previous data suggest that the prevalence of disability among older Puerto Ricans is among the highest in the United States and its territories. However, there are few systematic studies of late-life disability in Puerto Rico. This study aims to estimate the age-specific prevalence of disability among Puerto Rican older adults and present disability levels by gender, socioeconomic status (SES), and region. Data comes from the 2016 Public Use-Microdata of the American Community Survey. We estimated the age-specific prevalence of at least one disability among older adults in Puerto Rico and disability sub-categories. 49% of the elderly in Puerto Rico reported at least one disability in 2016. Physical disability was the most prevalent among sub-categories followed by Independent living. Females reported a higher prevalence of at least one disability and its sub-categories. Older adults in the lowest level of SES have higher disability prevalence compared to mid and high SES levels. The prevalence of disability is higher in the metro region (54%) followed by the capital (53%). The east region (41%) has the lowest prevalence. There is substantial heterogeneity in late-life disability among Puerto Rican older adults. Socioeconomic status, place of residence, and gender seem to play an important role in late-life disability. Future research is needed to identify the fundamental causes of late-life disability among Puerto Rican older adults.